THE EFFECT OF PROMOTION, PRICE, AND SERVICE QUALITY ON PURCHASE DECISION OF HIGHER EDUCATION SERVICE (CASE STUDY ANALYSIS AT “X” UNIVERSITY IN MALANG CITY) (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Universities became one of the most important things in education right now. In Indonesia there are more than 4.618 universities, this condition gives the prospective students have many choices and its causes an intense competition between each university. Customer (prospective students) purchase decision can be influenced by many factors, this research choose 3 dominant factors (promotion, price and service quality) to customer purchase decision either partially and simultaneously. As many as 320 people are selected to be the sample based on Slovin formula. Multiple Regression Method is used as data analysis, F-test and T-test used as hypothesis test. The result of the research show that simultaneously promotion and partially promotion, price and also service quality give significant effect on customer (prospective student) purchase decision, while price do not have significant influence on customer purchase decision. Service quality became the most dominant factor on customer purchase decision in choosing their ideal university.